Miliary tuberculosis in an immunocompetent adolescent - Pal, Swasti; Gupta, Alpa; Dhasmana, Renu; Saini, Manju; Khanduri, Rakhee; Bhat, N K (Indian Journal of Child Health, 2017)
Miliary tuberculosis (TB) is a rare form of TB, seen in approximately 1-2% of all the patients with TB. It represents hematogenous dissemination of uncontrolled TB. Human immunodeficiency virus (HIV) pandemic has led to resurgence of TB in both developed and developing countries. Without treatment, the mortality is near 100%. With early and appropriate treatment; however, mortality can be reduced to <10%. Early diagnosis increases the likelihood of a positive outcome. A 15-year-old boy presented to the outpatient department with complaints of dry cough and fever for 2 months, along with the history of anorexia and weight loss. Clinical workup showed mild pallor, hepatosplenomegaly, and choroid tubercles. Screening for HIV antibodies was negative. X-ray chest showed miliary opacities in the bilateral lung fields. Contrast enhanced computed tomography thorax showed multiple military nodules in both lung fields, tree in bud appearance, and multiple enlarged lymph nodes. The patient was treated with 4 drugs antitubercular treatment along with oral steroids. Follow-up after 1 month showed clinical improvement.